Exploring How User-Generated Content and Micro-Influencers Shape Buying Behavioral Intention - Kumari, Kavita; Kumar, Pankaj (PT Global Digital Sains Tekno, 2025)
Purpose: This study investigates how the buying behavioral intention of Generation X and Baby Boomers is influenced by the user-generated content (UGC) and micro-influencer endorsements. It addresses a gap in existing literature that usually focuses on younger demographics, aiming to understand how older consumers, especially for aged 35 and above, engage with social media marketing exposure. Method: A quantitative explanatory research design was employed, using a structured online survey distributed among Indian consumers aged 35 and above. The study adapted validated scales to measure UGC, micro-influencer credibility, and purchase intention. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess reliability, validity, and the strength of hypothesized relationships. Findings: The results reveal that both UGC and micro-influencer exposure significantly shape buying behavioral intentions among older consumers. Peer-generated content fosters trust and credibility, while micro-influencers—due to their relatability and authenticity—effectively influence purchase decisions. These findings challenge assumptions about digital disengagement among older age groups. Implication: Marketers should consider integrating UGC and collaborating with micro-influencers whose values align with older consumers. Tailored campaigns that emphasize clarity, credibility, and emotional resonance can enhance engagement and drive purchase behavior in this demographic. The study offers actionable insights for inclusive and age-sensitive digital marketing strategies. Originality: This research extends the applicability of social media marketing constructs to older consumer segments, offering an understanding of their decision-making processes. By focusing on Generation X and Baby Boomers, it contributes to a more comprehensive and representative view of consumer behavior in the digital age.